Teaching mathematics in the Paraense Amazon: with the word, teachers of early Childhood Education (Research, Society and Development, 2020)
The teaching of mathematics in early Childhood Education is of fundamental importance for the development of the child, since it allows the construction of their own knowledge by improving their cognitive abilities, memory, logical reasoning, among other skills essential for the formation of the individual. In this work we propose to investigate how the teachers of early childhood education have been contemplating such teaching at this stage of schooling, reflecting on what past experiences have marked their teacher training and what methodologies have been prioritized in their current practices. For this, we carried out a qualitative research, with five teachers of Early Childhood Education from some schools of the municipal education network of Belém - territory that contemplates our Paraense Amazon - which attend children in the age group of one to five years old. As research instruments, we use semi-structured interviews, from which we found that: the experiences of the teachers' student past can have an influence on their training and performance as well as other important events in their lives; who consider the teaching of mathematics as essential in the education of children and who seek different strategies to approach it. We conclude that the teaching of mathematics in the municipal public network of the Paraense Amazon has been developed through language projects, which demonstrates the significance of working with projects in early childhood education by favoring playful, innovative, contextualized and instigating practices that challenge children to understand mathematics in their daily lives.